Risk Assessment for Start-Up Business in SMEs: Qualitative and Mathematical Approach (Contemporary Mathematics, 2024)
Due to its crucial role in economic growth and job creation, there has been a notable increase in start-up businesses, particularly small and medium enterprises (SMEs). Many start-up entrepreneurs, however, struggle to sustain their businesses beyond the first five years, and some ultimately fail. This can be attributed to their various risks and challenges during their entrepreneurial journey. Consequently, risk management emerges as a valuable tool for entrepreneurs to identify and effectively address these risks. Hence, this research paper aims to devise a new mathematical formulation for the risk management index of start-up businesses in SMEs, employing qualitative and quantitative approaches. Interviews were conducted with experts to identify the risk factors specific to start-up businesses, and the data collected was subsequently analyzed using the Atlas ti software. Furthermore, a mathematical formulation for the risk management index was developed using a fundamental composite index formulation. The findings reveal the presence of five distinct risk factors in start-up businesses within SMEs. A mathematical formulation and a key indicator index were also established for assessing start-up business readiness in SMEs. These formulations and key indicator indexes are pivotal in enabling entrepreneurs to gauge their readiness for a new business venture. The findings contribute to alternative risk management tools for SMEs, especially for small businesses that are just getting started.
Keywords: risk factors; risk management index; SMEs; qualitative approach; atlas ti; mathematical modelling